Understanding Child Labor in Ghana Beyond Poverty : The Structure of the Economy, Social Norms, and No Returns to Rural Basic Education - Krauss, Alexander (World Bank, Washington, DC, 2013)
One in six children age 6-14 are engaged in labor activities in Ghana, with child employment being the leading alternative to schooling. By exploring structural, institutional, geographic, monetary, demographic, and cultural factors affecting household decisions about child labor, the paper's main purpose is to identify the conditions and characteristics of working children, the root causes of their vulnerability, and thus help to inform decision-makers and actors who draft and implement public policy of possible ways to tackle child labor in Ghana. The paper empirically assesses the effects of individual, household, community, regional, and national factors on child labor simultaneously. Findings from the analysis indicate that the underlying causes of child labor vary from factors as widespread in their influence as the structure of the economy (which is largely shaped by family farming), demographics and relevant social norms to those as specific in their manifestation as the geographic isolation of particular groups in the North, a lack of higher returns to schooling up to the basic education level in rural areas, and the low priority and capacity to enforce anti-child labor laws. In addition, an interview conducted with the Minister of Education as well as interviews with Ghanaian children help identify specific interdependencies between child labor and schooling and highlight the societal and economic demand for children to be working. Finally, after identifying which constraints and enabling factors are most important, the paper outlines policy and reform approaches to tackle child labor in Ghana.